Virtual functions in multihomed vehicular networks - Silva, Miguel Ângelo Pereira da (2019)
In the current Vehicular Ad-hoc Networks (VANETs), the number of services and applications being used by the vehicles and its occupants is increasing. Nowadays, the majority of the services and applications are located outside the vehicular network which may imply an additional delay in services that are delay sensitive (e.g. road safety). In addition to that, these applications and services become inaccessible whenever the vehicular network loses contact with the infrastructure. This dissertation presents a practical solution that aims to minimize the impact of these problems. The solution focuses on using Network Function Virtualization (NFV) technologies to support the deployment of services at the edge of a mobility-enabled multihomed VANET, thus allowing certain services to be accessible in intermittent connectivity situations, as well as ensuring lower delays for critical services. These services are made up of lightweight Virtual Functions (VxFs) that are deployed at the edge of the VANET, as close as possible to the users. To evaluate the performance of the proposed solution several test scenarios, as well as use cases were developed. The results obtained show that the solution is capable of deploying services at the edge of the VANET with low delay and with recovery when in handover and mobility situations. The uses cases developed show that, for example, for a service which encompasses a single vehicle, if the vehicle loses connection with the infrastructure, both the operation and usage of the service are not affected. The use cases also show that, services deployed using the solution have lower delay values when compared with the same services when they are available in the cloud.